Privatization of Education and Performance of Universities in Mogadishu, Somalia - AbdiHersi, Sayid - Ali (NIU Journal of Social Sciences; Vol 2 No 2 (2016): KIU Journal of Social Sciences, Vol. 2 No.2, September 2016, 2017)
The study investigated the role of privatization of education and performance of universities in Mogadishu-Somalia. This study used both secondary and primary data collection methods. It was established that there has been a significant growth in the higher education sector across Mogadishu. Although there are many positive aspects to this rapid growth given the initial conditions and recent history of the country, it raises serious concerns about the quality of education provided. It was suggested that there is need for a collaborative existence of educational associations and umbrella organizations to establish a cohesive national higher education policy aimed at streamlining standards, improving quality, and addressing fundamental deficiencies. The paper also opined that there is need for targeted incentives to universities to improve their research and publication capacity and output.